Giardia duodenalis infection and wastewater irrigation in Pakistan - Ensink, Jeroen H.J.; Hoek, Wim van der; Amerasinghe, Felix P. (2006)
The risk of Giardia duodenalis (Giardia) infection in farmers using untreated wastewater in agriculture was investigated in the city of Faisalabad, Pakistan, through a cross-sectional study. The study found a significantly increased risk of (asymptomatic) Giardia infection in wastewater farming households when compared with farming households using regular (non-wastewater) irrigation water (OR 3.3, 95% CI 2.5-4.4). Textile labourers who were employed in the city of Faisalabad but who lived in the same village as the wastewater farmers showed a risk of Giardia infection in between that of wastewater and non-wastewater farming households (OR 2.4, 95% CI 1.9-3.1). This study suggests that exposure to wastewater with high Giardia concentrations carries an increased risk for (asymptomatic) Giardia infection.